Diagnostic accuracy of computed tomography scan in renal cell carcinoma - Nahar, Shamsun; Mizanur Rahman, M.; Mahmud, Muhammad Sayeed; Obaedul H. Rafiq, S. M.; Sharmin, Shaila (International Journal of Research in Medical Sciences, 2023)
Background: Renal cell carcinoma (RCC) is becoming more common over the world. At the same time, numerous European and North American countries have achieved lower death rates. Methods: This cross-sectional observational study was conducted from July 2013 to June 2014 in the department of radiology and imaging of Dhaka Medical College Hospital. Clinically suspected 50 cases of renal cell carcinoma were included in this study. The study taken ethical clearance from the department and consent from the respondents. Statistical package for the social sciences (SPSS) software used for the analysis. Results: The mean age of the patients was 50.08±13.04 years. Male to female ratio was 2.1. More than half of the cases had hypodense lesion while 28% patients had calcification in the lesion. Mild enhancement was found in 56% cases and 50% were heterogenous in nature. Both nodal involvement and metastasis were limited. Computed tomography (CT) scan had 97.73% sensitivity and 100% specificity in diagnosis RCC. The diagnostic accuracy, positive predicative value and negative predicative values were 98%, 100% and 85.7 respectively. Conclusions: CT scan is a useful diagnostic modality in diagnosis of renal cell carcinoma.